Low Temperature Synthesis as a Route for Highly Thermoelectric Efficient Na‐Doped PbTe. Issue 17 (6th June 2018) - Papageorgiou, Chryssi; Delimitis, Andreas; Symeou, Elli; Giapintzakis, Ioannis; Kyratsi, Theodora
Abstract : In this work, Na‐doped PbTe is synthesized through a low temperature synthesis technique. This method provides highly efficient p‐type PbTe using a synthesis temperature much lower than the PbTe melting point and as low as 430 °C followed by sintering at 600 °C. A maximum ZT of 1.36 at 720 K is achieved for the Pb0.98 Na0.02 Te sample arising from a high power factor and a very low lattice thermal conductivity. The low thermal conductivity is attributed to the in situ nanostructuring achieved by the low temperature synthesis method, followed by cold pressing and sintering. Abstract : Na‐doped PbTe is synthesized through a low temperature synthesis technique. This method provides highly efficient p‐type PbTe with ZT of 1.36 at 720 K for the Pb0.98 Na0.02 Te. The low thermal conductivity is attributed to the in situ nanostructuring achieved by the low temperature synthesis method, followed by cold pressing and sintering.